Point-defect diffusion in a strained crystal - Tomé, Carlos N.; Ceccatto, Hermenegildo Alejandro; Savino, Eduardo José (American Physical Society, 1982)
Fil: Tomé, Carlos N. Comisión Nacional de Energía Atómica; Argentina